Enhancing the Performance of Lignocellulosic Textile Fabrics by Chemical Treatment and Filler Modification - Mahbub Morshed Khan; Md. Rokonuzzaman; Abu Sayeed; T. Islam; D. Paul; A.T.M. Gulam Moula; M.S. Jahan; S.C. Das (Journal of Natural Fibers)
To improve the durability of lignocellulosic jute textiles, the raw woven fabric (plain weave) was treated with alkali and aloe vera solution. A coating of unsaturated polyester resin was employed to protect the jute textiles from outdoor environmental degradation. The initiator for the resin was methyl ethyl ketone peroxide (MEKP). To further improve the performance of the polyester-coated jute textiles, 10% Ca(OH)2 fillers were mixed with the resin. Hence, the developed jute textile samples were – J0 (raw jute textile), J1 (alkali and aloe vera treated and polyester resin-coated jute textile), and J2 [Ca(OH)2 filler-modified textiles of J1]. The physico-mechanical characteristics of all the jute textile samples were examined and evaluated via tensile, moisture, and water uptake performances. It was revealed that tensile breaking strength increased by 56% and 129% for J1 and J2 textiles, respectively, compared to the J0. The filler content samples (J2) also demonstrated an enhanced moisture resistance performance compared to J0. Further characterization was performed using FTIR (Fourier Transform Infrared) spectroscopy, TGA (Thermogravimetric Analysis), and SEM (Scanning Electron Microscopy) analysis. The aging test demonstrated improved properties for the modified jute textile samples in acidic and salt solutions, but weight loss occurred in alkaline solutions.